A study on factors influencing the adoption of crop residues as cattle feed among farmers in Kelantan, Malaysia - Kamarudin, Muhammad Aidil Ikhwan; Abdullah, Farah Adila; Abdul Fatah, Fazleen; Ruslan, Nur Aziera; Kamarul Zaman, Nur Badriyah; T. Abu Bakar, Tengku Halimatun Sa’adiah (GADING Journal for the Social Sciences, 2025)
Utilising crop residues as cattle feed is a promising strategy for improving sustainability and reducing feed shortages in Malaysia’s cattle farming industry. This study investigates the factors influencing the adoption of crop residues among cattle farmers in Kelantan since the industry faces challenges including limited grazing land, high feed costs, and dependency on traditional feed sources. A quantitative research approach was employed involving structured interviews with 109 cattle farmers across six districts. Descriptive statistical analysis revealed a moderate proportion of farmers who recognise the benefits of crop residues, yet adoption remains constrained due to economic limitations, lack of awareness, and inadequate technical support. Many farmers perceive crop residues as cost-effective and beneficial for productivity; however, knowledge gaps and logistical constraints hinder widespread implementation. Findings suggest that targeted training programs, financial support and improved extension services are critical for increasing adoption rates. Encouraging the use of crop residues can enhance local cattle farming sustainability, reduce reliance on imported feed, and contribute to Malaysia’s food security objectives.